Innovation- driven hierarchical cultivation policy recommendations for technology - based enterprises in emerging Chinese cities: The case of Dezhou, Shandong Province - Yinping , Cai; Mohd Noor, Mohd Asri (Journal of Islamic, Social, Economics and Development, 2025)
This study investigates the innovation-driven hierarchical cultivation policies for technology-based enterprises (TBEs) in emerging Chinese cities, with a specific focus on Dezhou City in Shandong Province. Grounded in enterprise life cycle theory and enterprise growth theory, the study examines the developmental stages and challenges faced by TBEs and proposes a systematic policy approach for fostering innovation-oriented leading enterprises. The study finds that while Dezhou has achieved notable progress in TBE expansion, challenges persist, including insufficient high-level enterprises, weak basic research, inadequate credit evaluation systems, and underperforming incubation mechanisms. Updated to 2024 data, the study recommends enhancing enterprise hierarchy, strengthening R&D and innovation platforms, refining financing systems, and developing integrated high-tech industrial parks. The research offers theoretical and practical insights for implementing innovation-driven development strategies in regional economies.